“Are You Planning to Follow Your Route?” The Effect of Route Exchange on Decision Making, Trust, and Safety - Aylward, Katie; Weber, Reto; Man, Yemao; Lundh, Monica; MacKinnon, Scott N. (Journal of marine science and engineering, 2020)
The Sea Traffic Management (STM) Validation project is a European based initiative which focuses on connecting and updating the maritime world in real time, with efficient information exchange. The purpose of this paper is to evaluate two functions developed during the project: a ship to ship route exchange (S2SREX) function and rendezvous (RDV) information layer, collectively referred to as S2SREX/RDV. S2SREX displays the route segment consisting of the next seven waypoints of the monitored route of a collaborating ship and the RDV layer that predicts a meeting point. S2SREX/RDV provides supplementary information to data acquired by existing navigation systems and is intended to improve situational awareness and safety through a more comprehensive understanding of the surrounding traffic. Chalmers University of Technology and Solent University completed an experiment using twenty-four experienced navigators in bridge simulators. Six traffic scenarios were developed by subject matter experts and tested with and without S2SREX/RDV functionalities. Qualitative data were collected using post-test questionnaires and group debriefs to evaluate the participants’ perceptions of S2SREX/RDV in the various traffic scenarios, and quantitative data were collected to assess the ship distances and behavior in relation to the International Regulations for Preventing Collisions at Sea (COLREGs). The results revealed that participants generally trusted the S2SREX/RDV information, and most used S2SREX/RDV for decision support. The quantitative assessment revealed that the COLREGs were breached more often when S2SREX/RDV was used. Experimental findings are discussed in relation to safety, trust, reliance, situational awareness, and human-automation interaction constructs.